2016
DOI: 10.1007/s00167-016-4282-z
|View full text |Cite
|
Sign up to set email alerts
|

Credibility and quality of meta-analyses addressing graft choice in anterior cruciate ligament reconstruction: a systematic review

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…8,25,32,39,40 However, it has been reported that the credibility and quality of published meta-analyses have been limited. 25 As a result, it is recommended that decisions regarding graft choice be made on an individual basis, taking into account patient factors and preferences, surgeon experience, and the best available evidence. 25 Recently, several authors have reported a multitude of advantages of combined ACL and anterolateral ligament (ALL) grafts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,25,32,39,40 However, it has been reported that the credibility and quality of published meta-analyses have been limited. 25 As a result, it is recommended that decisions regarding graft choice be made on an individual basis, taking into account patient factors and preferences, surgeon experience, and the best available evidence. 25 Recently, several authors have reported a multitude of advantages of combined ACL and anterolateral ligament (ALL) grafts.…”
mentioning
confidence: 99%
“…25 As a result, it is recommended that decisions regarding graft choice be made on an individual basis, taking into account patient factors and preferences, surgeon experience, and the best available evidence. 25 Recently, several authors have reported a multitude of advantages of combined ACL and anterolateral ligament (ALL) grafts. These advantages have been attributed to load sharing with the ACL graft and improved knee kinematics.…”
mentioning
confidence: 99%
“…A review analyzing these 17 meta-analyses have been published and concluded there to be insufficient evidence to recommend for or against either graft. 33 However, these meta-analyses have been performed on both female and male patients, and no single systematic review or metaanalysis has focused on female patients alone. Three other reviews have looked into the influence of gender on the outcomes of ACL reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review by Kurz et al. 24 reporting on the credibility and quality of meta-analyses addressing graft choice in ACLR, the investigator reported limited credibility of some of the included studies, with a trend toward earlier studies having limited methodological “rigor.” More high-quality studies are needed to evaluate graft choice in ACLRs and improve surgical techniques, coupled with biological approaches to ultimately improve the return to activities of the patients. Historically, most knee arthroscopists debated the indications and benefits of patellar tendon and hamstring autografts.…”
Section: Discussionmentioning
confidence: 99%